A case of mesonephric adenocarcinoma of the vagina with a 1-year follow-up. Issue 5 (1st August 2008) - Bifulco, G.; Mandato, V. D.; Mignogna, C.; Giampaolino, P.; Di Spiezio Sardo, A.; De Cecio, R.; De Rosa, G.; Piccoli, R.; Radice, L.; Nappi, C.
Abstract : Mesonephric adenocarcinoma deriving from remnants of vaginal mesonephric ducts is one of the rarest tumors of the female genital tract with only three cases reported till date in international literature. Differential diagnosis from other aggressive tumors is complex and controversies exist in the literature regarding the biological behavior, prognosis, and optimal management strategies of these tumors. A 58-year-old woman presented with a large mass extending from the right adnexal region to the perineum and labia majora. CA125 was increased. A radical excision of the lesion with pelvic and para-aortic lymphadenectomy was performed. A well-capsulated mesonephric adenocarcinoma in a background of vaginal mesonephric remnants was diagnosed. Tumor cells showed immunoreactivity for pancytokeratin, cytokeratin (CK), CD 10, epithelial membrane antigen, vimentin, and calretinin; indeed they were negative for carcinoembryonic antigen, CK 20, estrogen receptor, and progesterone receptor. No evidence of lymph node involvement or metastatic disease was observed. The patient did not receive any adjuvant therapy and is alive and clinically free of disease at 1-year follow-up. In spite of the aggressive biological behavior attributed in literature to mesonephric carcinomas, which is probably due to the complex differential diagnosis with other müllerian tumors, the favorable course of our patient further supports the hypothesis that malignant mesonephric carcinomas may not behave aggressively and that radical surgery alone may be curative